Functional MRI of Sensorimotor Cortex in Preterm Infants - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2009)
Functional MRI (fMRI) findings in a group of 5 pre-term infants were correlated with a unilateral passive forearm extension/flexion to relate the functional data to structural and behavioral data, in studies at the University of Bonn, Germany; and University Medical Center, Groningen, Netherlands.